STRATEGY FOR THE DEVELOPMENT OF INMATES AT CLASS IIB BOYOLALI STATE PRISON - Al Hakim, Maulana Akbar; Pangestuti, Naniek (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study discusses the rehabilitation strategies for inmates at the Class IIB Boyolali State Detention Center, which include programs for self-sufficiency, personality development, and collaboration with external institutions such as the Ministry of Religious Affairs, universities, and religious organizations. These programs aim to prepare inmates for reintegration into society after their sentence. However, the implementation faces various challenges, such as budget limitations, inadequate facilities, a lack of qualified personnel, and overcrowding. These limitations hinder the quality of rehabilitation and training programs. Collaboration with external parties is viewed as a strategic solution, allowing for the utilization of additional resources and the development of higher-quality programs. Furthermore, the use of technology such as e-learning, regular evaluations, and private sector involvement is expected to enhance the effectiveness of rehabilitation programs. Proposed solutions include training outside the detention center, providing additional instructors, and engaging the private sector in offering job opportunities for inmates. With this approach, it is hoped that inmates can receive better support for skill development and successful social reintegration. Keywords: Inmate Rehabilitation; External Collaboration; Overcrowding